Nationally representative surveys show gradual shifting of overweight and obesity towards poor and less-educated women of reproductive age in Nepal - Sutradhar, Ipsita; Akter, Tahmina; Hasan, Mehedi; Gupta, Rajat Das; Joshi, Hemraj; Haider, Mohammad Rifat; Sarker, Malabika (Cambridge University Press, 2022)
This article was published in Cambridge University Press [ © The Author(s) 2020. Published by Cambridge University Press] and the definite version is available at: https://doi.org/10.1017/S0021932020000152 The Journal's website is at: https://www.cambridge.org/core/journals/journal-of-biosocial-science/article/nationally-representative-surveys-show-gradual-shifting-of-overweight-and-obesity-towards-poor-and-lesseducated-women-of-reproductive-age-in-nepal/4D844679369245AAEE4F6B27565045B6